Oncologic and Safety Outcomes for Retrograde and Antegrade Endoscopic Surgeries for Upper Tract Urothelial Carcinoma: A Systematic Review and Meta-analysis - Laukhtina, Ekaterina; Kawada, Tatsushi; Quhal, Fahad; Yanagisawa, Takafumi; Rajwa, Pawel; von Deimling, Markus; Pallauf, Maximilian; Bianchi, Alberto; Majdoub, Muhammad; Enikeev, Dmitry; Fajkovic, Harun; Teoh, Jeremy Yuen-Chun; et al. (European urology focus, 2023)
The aim of this study was to identify and summarize available data on oncologic and safety outcomes for retrograde versus antegrade endoscopic surgery in patients with upper tract urothelial carcinoma (UTUC). We systematically searched studies reporting on endoscopic surgery in patients with UTUC. The primary outcome of interest was oncologic control, including bladder and upper urinary tract recurrences. The secondary outcomes were any-grade and major complications. Twenty studies comprising 1091 patients were included in our analysis. The pooled bladder recurrence rate was 35% (95% confidence interval [CI] 28.0-42.3%; I2 = 48%) after retrograde endoscopic surgery and 17.7% (95% CI 6.5-32.1%; I2 = 29%) after antegrade endoscopic surgery. The pooled upper urinary tract recurrence rate was 56.4% (95% CI 41.2-70.9; I2 = 93%) after retrograde endoscopic surgery and 36.2% (95% CI 25.5-47.6%; I2 = 57%) after antegrade endoscopic surgery. The pooled complication rate was 12.5% (95% CI 0.8-32.8%; I2 = 94%) for any-grade complications and 6.6% (95% CI 0.1-19.1%; I2 = 89%) for major complications in the retrograde endoscopic cohort. In summary, our analyses suggest promising oncologic benefits of antegrade kidney-sparing surgery in terms of bladder and upper urinary tract recurrence rates in UTUC. Retrograde endoscopic surgery is a safe procedure with a minimal risk of complications and acceptable oncologic outcomes. Research should address the hypothesis that endoscopic antegrade surgery can be a safe and effective alternative for well-selected patients. PATIENT SUMMARY: One of the surgical options for treatment of cancer of the upper urinary tract is removal of the tumor through a small telescope called an endoscope. The endoscope can be inserted via the urethra (called a retrograde approach) or through a small incision in the skin (antegrade approach). Our review shows that the antegrade approach seems to provide acceptable cancer control rates. Further research could help to identify the role for endoscope surgery in cancer of the upper urinary tract.
Keywords: nádory ledvin; ureteroskopie; Kidney-sparing surgery; Ureteroscopy; Upper tract urothelial carcinoma; Humans; nádory močovodu; Ureteral Neoplasms; Antegrade; Endoscopic surgery; nádory močového měchýře; lidé; Urinary Bladder Neoplasms; Retrograde; Kidney Neoplasms; Carcinoma, Transitional Cell; karcinom z přechodných buněk